The Existence and Multiplicity of Normalized Solutions for Kirchhoff Equations in Defocusing Case (Analysis in Theory and Applications, 2024)
In this paper, we study the existence of solutions for Kirchhoff equationwith mass constraint conditionwhere $a$, $b$, $c>0$, $μ\in \mathbb{R}$ and $2
Keywords: Normalized solutions; Kirchhoff-type equation; mixed nonlinearity.